Body mass index and the use of the Internet for health information. (February 2016) - Faith, Jennifer; Thorburn, Sheryl; Smit, Ellen
Objective: Individuals who experience or anticipate negative interactions from medical providers related to conditions such as obesity may preferentially use the Internet for health information. Our objectives in this study were to (1) examine the association between body mass index (BMI) and Internet health information–seeking and (2) examine whether the association between patient-centred communication and Internet health information–seeking differed by BMI category. Method: We used data from the Health Information National Trends Survey 3 ( n  = 7, 674), a cross-sectional nationally representative survey of US adults. Using weighted data, we determined associations between BMI category and Internet health information–seeking, adjusting for sociodemographic and health-related variables. We then determined the adjusted associations between patient-centred communication and Internet health information–seeking stratified by BMI category. Results: Most (78.7%) sought health information from the Internet. The odds of Internet health information–seeking among individuals with overweight (adjusted odds ratio [AOR] = 0.96) and individuals with obesity (AOR = 1.45) did not differ significantly from individuals with normal weight. The association between perceived levels of patient-centred communication and using the Internet for health information did not differ by BMI category. Conclusion: Study findings suggest that most individuals seek health information from the Internet. Despite non-significant results, this study points to the need for research on health information choices specific to weight loss among individuals with overweight and obesity using more comprehensive measures of the frequency, preference and motivation for information-seeking.